Is God Christian? : Christian identity in public theology: an Asian contribution - Niles, D. Preman (Fortress Press, 2017)
Is God Christian? Christian Identity in Public Theology: An Asian Contribution is a sequel to Niles's previous book, The Lotus and the Sun: Asian Theological Engagement with Plurality and Power, and continues the narrative of the social biography of Asian theology. It enters the theological efforts of the author's generation as a collective enterprise to survey methods that in the arena of public theology confront and reject the assertion that God is Christian or there is a Christian god among other gods. The focus is on the issues and questions that affect the people and societies of Asia. The theology envisaged here is not the kind that will confine itself within the Christian community but one that will have an import for the actors in public life. Asian Public Theology will be one that will be inherently interreligious in nature. Accordingly, the theological methods explored in this book are not concerned narrowly with problems in Christian theology, but rather with challenges posed for Christian theology in the wider arena of social and political life in Asia.